Phytochemical characterization and mushroom tyrosinase inhibition of different extracts from Salvia officinalis L. leaves. - Lana Y.M. Juee (GarVal Editorial Ltda., 2022)
Context: Sage (Salvia officinalis) is an ancient valuable plant used in the treatment of variant health issues. Aims: To evaluate the depigmentation activity of S. officinalis leaf chloroformic (SOCF) and ethanolic (SOMF) extracts via its efficacy to inhibit tyrosinase enzyme using in vitro model and bioassay-guided identification and quantification of the main active constituents. Methods: Plant extracts efficacy as a depigmentation agent has been studied via mushroom tyrosinase inhibition using in vitro model at two concentrations (100 and 200 µg/mL). Extracts were analyzed for phenolic compounds that could be responsible for the biological activity using LC-MS/MS analysis. Results: Significant potency at a high concentration of 200 µg/mL for the methanolic extract were recorded (p≤0.05). The LC-MS/MS analysis of S. officinalis leaf extracts revealed the presence of eight and fourteen analytes of origin of thirty-seven analytes in both SOCF and SOMF, respectively. Analytes' quantification recorded the highest amount for rosmarinic acid (46 016 µg/g) in SOMF and the lowest was hesperidin (0.6 µg/g) in SOCF. Conclusions: S. officinalis extracts recorded significant tyrosinase inhibition potency could control the melanin synthesis process and exhibit beneficiary effect in hyperpigmentation issues.